Incidence and Course of Symptomatic Deep Venous Thrombosis of the Lower Extremities in a Black Caribbean Population - Nossent, J C; Egelie, N.C W.M (Thrombosis and Haemostasis, 1993)
During a 5-year period 131 patients with symptomatic deep venous thrombosis of the lower extremities (DVT) were identified in a black Caribbean population. Eighty-one patients (61%) had objective evidence (ascending venography), while in 39% the diagnosis was based on clinical findings only. The overall annual incidence rate for definite DVT was 11 per 100,000 person years; there was a steep increase with age in both sexes. Proximal DVT was present in 69% of patients. Swelling (92%), pain on palpation (89%) and tenderness (87%) were the most frequent symptoms, while immobilization (43%) and varicosities (42%) were the most frequent risk factors; DVT was rare during pregnancy (1 in 15,000 deliveries). Seventeen patients (21%) developed pulmonary embolism and five patients (6.2%) died during the hospital stay (four of fatal pulmonary embolism, one due to toxic epidermolysis after venography). We conclude, that symptomatic DVT of the lower extremities has a low incidence in this black Caribbean population, but is nonetheless associated with considerable morbidity and mortality due to pulmonary embolism.